REVITALISASI PERMAINAN TRADISIONAL MELALUI POJOK MAIN: UPAYA PELESTARIAN BUDAYA LOKAL DAN PENGUATAN KARAKTER SISWA DI SDN 104245 TUMPATAN - Bunga Ananda; Siti Chairunisa; Asep Prima (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
The rapid development of digital technology has led children to prefer gadget-based games rather than traditional ones that are rich in cultural values. This situation threatens the continuity of local cultural heritage and weakens children’s social character development. The Traditional Play Corner program at SDN 104245 Tumpatan serves as an effort to revitalize traditional games in an educational setting. This article aims to describe the implementation strategy and benefits of the Play Corner program in preserving local culture and strengthening students’ character. This study employs a literature review approach by analyzing various relevant sources on traditional games, character education, and local wisdom-based learning. The findings indicate that Play Corner enhances social interaction, fosters responsibility, sportsmanship, and cooperation among students, while also nurturing appreciation for local culture. Revitalizing traditional games provides an effective means to instill cultural values and national character from an early age.